Functional analysis of microorganisms and metabolites in the cecum of different sheep populations and their effects on production traits - Meng, Quanlu; Tang, Zhixiong; Yang, Feifei; Shi, Jinping; Liu, Ting; Cheng, Shuru (Frontiers in Microbiology, 2024)
The purpose of this study was to investigate the effects of intestinal microbiota on the growth and production performance of different groups of sheep, focusing on the role of cecal microbiota in regulating intestinal function, enhancing digestion and absorption, and improving feed utilization. The production performance of MG×STH (Mongolia × Small Tailed Han) F1 hybrids and purebred STH (Small Tailed Han) sheep by measuring various factors, including enzyme activities and VFAs (volatile fatty acids), to analyze changes in cecal fermentation parameters across different sheep groups. Metagenomic and metabolomic sequencing combined with bioinformatics to analyze the cecal contents of the two sheep populations. The study findings indicated that the MG×STH F1 hybrids outperformed the purebred STH in terms of body weight, height, oblique body length, and VFAs (P < 0.05). Additionally, the MG×STH F1 higher levels of protease and cellulase in the cecum compared to the purebred sheep (P < 0.05). Metagenomic analysis identified 4034 different microorganisms at the species level. Five differential organisms (Akkermansiaceae bacterium, Escherichia coli, unclassified p Firmicutes, Streptococcus equinus, Methanobrevibacter millerae) positively regulated sheep performance. Metabolomics identified 822 differential metabolites indoleacetaldehyde, 2-aminobenzoic acid, phenyl-Alanine, enol-phenylpyruvate and n-acetylserotonin were associated with improved performance of sheep. The combined results from the metagenomic and metabolomic studies suggest a positive correlation between specific microbes and metabolites and the performance of the sheep. In conclusion, the MG×STH F1 hybrids demonstrated superior growth performance compared to the purebred STH sheep. The identified microorganisms and metabolites have promising roles in positively regulating sheep growth and can be considered key targets for enhancing sheep performance.